2009
DOI: 10.1007/s12206-008-1006-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shoulder geometry on residual stress and fatigue properties of AA6082 fsw joints

Abstract: The tool geometry is a crucial characteristic of the friction stir welding (FSW) process; its design is the key to the successful FSW application for a wide range of materials and thicknesses improving the weld strength and fatigue life. The present study investigates the influence of three shoulder geometries on the FSW joint performance, in terms of residual stresses state, microhardness profile and mechanical properties of 1.5 mm thick AA 6082-T6 FSW joints in the butt-joint configuration. The three tool ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…5, the lowest torque values are registered in welds carried out with the flat shoulder tool, for all welding parameters, which suggest that it is this tool that generates most heat, producing the maximum shear stress reduction of the material under the tool. These results are in good agreement with those of De Giorgi et al (2009), referred to above. However, a contradiction in the present study can be found by comparing torque results and the morphology of the welds, i.e., if the flat shoulder generates more heat, it should not lead to defects, contrary to what was observed in all welds produced with this tool.…”
Section: Discussionsupporting
confidence: 93%
“…5, the lowest torque values are registered in welds carried out with the flat shoulder tool, for all welding parameters, which suggest that it is this tool that generates most heat, producing the maximum shear stress reduction of the material under the tool. These results are in good agreement with those of De Giorgi et al (2009), referred to above. However, a contradiction in the present study can be found by comparing torque results and the morphology of the welds, i.e., if the flat shoulder generates more heat, it should not lead to defects, contrary to what was observed in all welds produced with this tool.…”
Section: Discussionsupporting
confidence: 93%
“…Heat is generated between the tool and material which leads to a very soft region near the FSW tool. The forging forces caused by the rotating tool deform the material plastically and correspondingly result in the "stirring" of the material in the nugget and joining of the workpieces [2]. This process induces large shear forces in the plastically deformed material, and subsequently raises the temperature of the material to approximately 0.6-0.7 T m (T m is the melting point of material).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a systematic bibliographical investigation was carried out to collect fatigue results generated by testing specimens made of 6056-T4, 6061-T6, 6082, 6082-T6 and 6082-T4. These specimens had been manufactured using different combinations of the key welding process parameters [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The thickness of the FS plate in these data ranged from 0.8-7 mm and the fatigue testing used load ratios of -1, 0, 0.1, 0.2, and 0.5.…”
Section: Fatigue Behaviour Under Pure Axial and Pure Torsional Cyclicmentioning
confidence: 99%